Key success factors and process for IT project portfolio management - Radchenko, Andryi (My University, 2011)
The importance of Information Technology (IT) in the business environment is continuously growing. This stimulates the increase of size, complexity and number of IT projects and raises the need for IT Project Portfolio Management (IT PPM). While being actively discussed for the last few decades, IT PPM has a short history of practical implementation. This creates inconsistency in the views of different authors and provides an opportunity for additional research. As a first step, this research explores the existing studies and brings together the views of different authors on IT PPM. As a result, a high-level IT PPM Process Cycle and a set of Key Success Factors for IT PPM are proposed. IT PPM Process Cycle gives an overview of the main elements of IT PPM process, while the set of Key Success Factors provides a number of factors that should be considered during the implementation. As a second step, both theoretical deliverables are empirically tested by a case study and a survey conducted in a big multinational company. The case study is used to analyze process framework of the studied company towards the developed IT PPM Process Cycle. Subsequently, a survey was conducted among subject matter experts of the same company to evaluate the importance and relevance of the proposed Key Success Factors. Finally, this thesis concludes with findings made during the case study and provides an empirically tested selection of factors to be taken into account. These two deliverables can be used by both academics and practitioners to close the gaps in existing literature and assist in IT PPM implementation.